Evaluation of risk factors for atherosclerosis using carotid ultrasonography in Japanese patients with rheumatoid arthritis. (17th May 2019) - Yamamoto, Hiroko; Nakajima, Toshiki; Kawahara, Rie; Nakabo, Shuichiro; Hashimoto, Motomu; Yamamoto, Wataru; Masuda, Izuru; Ito, Hiromu; Mimori, Tsuneyo; Fujii, Yasutomo
Abstract: Aim: Previous studies have reported that patients with rheumatoid arthritis (RA) have a higher risk of developing cardiovascular disease (CVD) than the general population. A major cause of CVD is atherosclerosis, which can be evaluated with carotid ultrasonography (US). As far as we know, there have been no large‐scale carotid artery US studies in Japanese patients with RA. The aim of this study was to identify the risk factors for atherosclerosis in Japanese patients with RA. Methods: The study subjects underwent physical examinations, laboratory tests and US examination, and answered a questionnaire about their lifestyle. Carotid US was performed to measure the maximum carotid intima media thickness (max cIMT) and to detect plaques. Results: Atherosclerosis was detected in 238 patients (52%). Age, hypertension, and total/high‐density lipoprotein cholesterol ratio were positively related to max cIMT. Presence of plaques was related to age, Disease Activity Score of 28 joints—erythrocyte sedimentation rate (DAS28‐ESR), smoking, and any biological treatment. DAS28‐ESR correlated positively not with cIMT but with the development of plaques in our patients with low disease activity (average DAS28‐ESR of 2.7). Conclusion: Disease Activity Score of 28 joints—erythrocyte sedimentation rate was related to the size and number of plaques, whereas only traditional risk factors were related to max cIMT. This indicated that the inflammatory conditions of RA could affect the formation of atherosclerotic plaques. For the management of CVD in patients with RA, it may be important to control not only traditional risk factors, but also RA disease activity.